Coldness Presentation Depending on Motion to Enhance the Sense of Presence in a Virtual Underwater Experience - Kenta Ito; Yuki Ban; Shin'ichi Warisawa (IEEE Access, 2022)
In virtual reality (VR), there is consumer demand for underwater world experiences. To address this demand, previous studies have presented coldness to enhance the sense of presence in virtual underwater experiences. We considered that we could further improve the sense of presence and the experiential quality of underwater VR simulations by making the coldness presentation more realistic. We also considered that methods of presenting coldness continuously would have a wider application range. In this research, with reference to actual water behavior, we propose a method that presents coldness depending on whether it is moving. We conducted an experiment comparing the sense of presence between the steady-state temperatures of $24.9 ± 1.9 \mathrm { ^{°}C} / 27.8 ± 2.7 \mathrm { ^{°}C}$ and the proposed method, the temperature of which moves between the aforementioned temperatures as the user moves and stops. The results show that the proposed method yielded higher scores than the higher steady-state temperature in “closeness of overall sensation” and “closeness of thermal sensation”. For the lower steady-state temperature, the proposed method achieved the same sense of presence improvement while removing less heat. This extends the experiential duration. Meanwhile, for those who noticed the temperature change, the proposed method yielded higher scores than the lower steady-state temperature in “realness” and “closeness of thermal sensation”. To further improve effectiveness of the proposed method, it is important to not only change the temperature but also to notice the temperature change. This method is suitable for several virtual underwater applications, such as education and training.